Research priorities for European paediatric emergency medicine - Bressan, Silvia (Arch Dis Child, 2019)
OBJECTIVE: Research in European Paediatric Emergency Medicine (REPEM) network is a collaborative group of 69 paediatric emergency medicine (PEM) physicians from 20 countries in Europe, initiated in 2006. To further improve paediatric emergency care in Europe, the aim of this study was to define research priorities for PEM in Europe to guide the development of future research projects. DESIGN AND SETTING: We carried out an online survey in a modified three-stage Delphi study. Eligible participants were members of the REPEM network. In stage 1, the REPEM steering committee prepared a list of research topics. In stage 2, REPEM members rated on a 6-point scale research topics and they could add research topics and comment on the list for further refinement. Stage 3 included further prioritisation using the Hanlon Process of Prioritisation (HPP) to give more emphasis to the feasibility of a research topic. RESULTS: Based on 52 respondents (response rates per stage varying from 41% to 57%), we identified the conditions ‘fever’, ‘sepsis’ and ‘respiratory infections’, and the processes/interventions ‘biomarkers’, ‘risk stratification’ and ‘practice variation’ as common themes of research interest. The HPP identified highest priority for 4 of the 5 highest prioritised items by the Delphi process, incorporating prevalence and severity of each condition and feasibility of undertaking such research. CONCLUSIONS: While the high diversity in emergency department (ED) populations, cultures, healthcare systems and healthcare delivery in European PEM prompts to focus on practice variation of ED conditions, our defined research priority list will help guide further collaborative research efforts within the REPEM network to improve PEM care in Europe.